PEMURNIAN DAN KARAKTERISASI GLISEROL HASIL SAMPING PRODUKSI BIODIESEL KEMIRI SUNAN - Pirdani Nur Fitri; Sarifah Nurjanah; Asri Widyasanti (Universitas Muhammadiyah Tangerang, 2019)
As world biodiesel production increases, glycerol production as a by product of the biodiesel production process also increases. Glycerol is a compound that is widely used in the pharmaceutical industry, care products, food, and cosmetics. Philippine tung is one of the sources of biodiesel raw material which is very potential to be developed in Indonesia and the yield of glycerol produced from the transesterification process can reach 19%. This study aims to purify and determine the characteristics of glycerol as a by-product of philippine tung biodiesel production. Glycerol quality analyzed included appearance, glycerol content, KOH content, soap content, water content and density. Based on the results of the research, it is known that the characteristics of glycerol as a byproduct of philippine tung biodiesel production are viscous dark liquid appearance, 2,6348% glycerol content, 2,4160% KOH content, 11,9563% soap content, 10,3441% moisture content, and 1,0955 density, while the characteristics of glycerol after neutralization has appearance of light brown viscous liquid, 87.8913% glycerol content, 11.8576% moisture content, and 1.2537 density. In addition, the yield of purification process also calculated, included neutralization yields of 90.6195%, separation yield of 39,3090%, and total yield of 38,6842%.Keywords: Glycerol, Purification, Philippine Tung, Characterization